(untitled) (Journal of Hama University, 2019)
The aim of this research was to study the pathological changes post vaccination by two different IBDV vaccine strains in broiler chickens. Three group of broiler chickens of one-day old were rearing to forty-two days, and each group was included 50 birds. First group (control) was unvaccinated, second group was vaccinated with Intermediate strain of Infectious Bursal disease at 14 days and third group was vaccinated with Infectious Bursal disease vaccine(Intermediate plus strain) at 14 days. Five birds were weighed from each group at (12-17-21-28-31) days, and Clinical Signs and Gross Lesions were observed on birds. Bursa of Fabricius was weighed and bursal index (BI) was calculated. The results were showed a non-significant difference in birds weights of three groups (P > 0.05 ), and pathological changes were showed in group vaccinated with Infectious Bursal disease vaccine (Intermediate plus) compared with other groups, and bursal index (BI) was showed significant differences in group vaccinated with Infectious Bursal disease (Intermediate plus) compared to the group vaccinated with Infectious Bursal disease vaccine (Intermediate strain) and control group ( P< 0.05). The study was showed Clinical Signs and Gross Lesions in birds vaccinated with Infectious Bursal disease vaccine (Intermediate plus), and a non-significant difference in bird weight in all three groups.